2023
DOI: 10.1029/2022jd038082
|View full text |Cite
|
Sign up to set email alerts
|

Upward Leaders Initiated From Instrumented Lightning Rods During the Approach of a Downward Leader in a Cloud‐To‐Ground Flash

Abstract: In this paper we analyze electric‐field and current measurements of upward leaders induced by a downward negative lightning flash that struck a residential building. The attachment process was recorded by two high‐speed cameras running at 37,800 and 70,000 images per second and the current measured in two lightning rods. Differently from previous works, here we show, for the first time, current measurements of multiple upward leaders that after initiation propagate to connect the negative downward moving leade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…The 2-D speed of NCL increases from 2.2 × 10 5 to 12.8 × 10 5 m/s (by a factor of 5.8), with an average of 7.3 × 10 5 m/s, and the 3-D speed of NCL increases from 2.2 × 10 5 to 15.3 × 10 5 m/s (by a factor of 7.0), with an average of 8.5 × 10 5 m/s (see Figure S4 in Supporting Information S1). That is consistent with previous reports on UCLs initiated from tall objects with its speed being increased with time (e.g., et al, 2014;Lu et al, 2013Lu et al, , 2015Qi et al, 2021), while it is contrary to UCLs observed on common buildings with the speed being approximately constant (e.g., Saba et al, 2017Saba et al, , 2022Saba et al, , 2023.…”
Section: -D Development Characteristics Of the Leaderssupporting
confidence: 93%
See 2 more Smart Citations
“…The 2-D speed of NCL increases from 2.2 × 10 5 to 12.8 × 10 5 m/s (by a factor of 5.8), with an average of 7.3 × 10 5 m/s, and the 3-D speed of NCL increases from 2.2 × 10 5 to 15.3 × 10 5 m/s (by a factor of 7.0), with an average of 8.5 × 10 5 m/s (see Figure S4 in Supporting Information S1). That is consistent with previous reports on UCLs initiated from tall objects with its speed being increased with time (e.g., et al, 2014;Lu et al, 2013Lu et al, , 2015Qi et al, 2021), while it is contrary to UCLs observed on common buildings with the speed being approximately constant (e.g., Saba et al, 2017Saba et al, , 2022Saba et al, , 2023.…”
Section: -D Development Characteristics Of the Leaderssupporting
confidence: 93%
“…Saba et al. (2023) reported that a DNL had a constant 2‐D speed (2.85 × 10 5 m/s) and twice faster than the speed of UCL, which is consistent with the results reported by Visacro et al. (2017a, 2017b) from four natural DNLs before attachment.…”
Section: Observations and Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…It is worth noting that the lack of branching in the UL is by design. Although the overall UL channel tends to be toward the DL because of the attraction between positive and negative leaders (Saba et al, 2023), the propagation direction of UL may change several times in a flash event (Figures 2b-2d), which is similar to the development of leaders recorded by cameras (Qi et al, 2019;Saba et al, 2017;Warner, 2010). When the final jump condition is reached, LAMM can reproduce two basic leader connection scenarios documented in the optical data, namely, the tip of DL to the tip of upward connecting leader (Figures 2a-2d) and the DL's tip to the lateral surface of UL (Figure 2b) (Lu et al, 2013(Lu et al, , 2016.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…A velocity ratio was adopted in this work and not absolute velocity values as an engineering approach; it is noted that most lightning attachment models from literature consider a constant speed ratio. However, recent high-speed video records [52], [53], [54], [55], [56] have shown a dynamic variation of downward and upward leader velocities; actually, velocity ratios even lower than unity were recorded [52], [54], [55]. In this work, a dynamic velocity ratio formula is employed based on the expression proposed in [12] and modified in [49] to account for recent field observations on downward and upward leader velocity ratios (allowing also for values lower than unity) and consider the effect of atmospheric conditions.…”
Section: B Parameter Selectionmentioning
confidence: 99%